Ready for global success? Strengths and weaknesses of Korean HRM - Fabian Jintae Froese (Asian Business & Management, 2020)
Fueled by a highly dedicated and highly skilled workforce, South~Korea (henceforth Korea)~has enjoyed tremendous economic growth and developed numerous successful global companies. In the past, Korean companies benchmarked Japanese and US HR practices. However, Korean companies are now at the crossroads, facing slowing economic growth rates, an aging population, changing gender roles, and an increase in foreign employees. This article reviews the strengths and weaknesses of Korean HRM and presents some tentative recommendations how Korean companies can respond to these challenges. If Korean companies intend to continue their global success, they are recommended to adapt their staffing strategy, organizational culture, and corporate language policies to embrace an increasingly diverse workforce.
Keywords: 650; Korea; Human resource management; Global talent management; Human resource practices; Staffing; Organizational culture